Identification of geochemical anomalies by the use of concentration-area (C-A) fractal model in Nakhilab region, SE Iran. (2017) - Daya, Ali Akbar; Boomeri, Mohammad; Mazraee, Nafiseh
Delineating the geochemical anomalies from the background is a fundamental task in geochemical exploration. Fractal methods are very useful methods for such purposes. This paper is devoted to separate geochemical anomalies from the background based on stream sediments data by utilising the concentration-area (C-A) fractal model in Nakhilab region, SE Iran. Stream sediments data were used in this study which was conducted for the primary regional exploration for Au, As, Ag, Cu in Nakhilab region. Log-log plots for the mentioned elements were drawn. Threshold values for the region were computed based on these log-log plots. The thresholds were identified for elements. Results showed that C-A method was capable for separation anomaly from the background. Correlation between geological map and results from C-A fractal model reveals that the anomalous areas are situated in sand, silt, and conglomerate in western and central parts of the area.